Growing up poor(ly): intergenerational class-based parenting logic in Singapore. Issue 2 (4th March 2023) - Ng, Irene Y. H.; Khoo, Joshua; Ng, Nicole
ABSTRACT: Class-based parenting logic transcends national culture. This is what we found when applying Laureau's (2011. Unequal childhoods: Class, race, and family life with an update a decade later (2nd ed.). University of California Press) schema of concerted cultivation for middle/higher class families and accomplishment of natural growth for working-class families to young parents in Singapore. Through in-depth interviews with 10 low-SES parents and eight high-SES parents between the ages of 27 and 37, we found Laureau's distinctions evident even in this young Asian country where the middle class has only recently emerged. Interviewing young adults at a stage in life when they were forming their parenting ideals, the intergenerational transmission of logics was apparent. So were constraints of work and earnings in shaping the intergenerational logics. The findings suggest that improving outcomes of low-SES children requires going beyond parenting programmes to tackling structures in society that harden class lines, e.g. education and work systems.